Surgical Management of Heart Failure - Wayne, Stephanie L.; Zimmet, Adam D. (Current Cardiology Reviews, 2021)
Optimal management of heart failure is collaborative, with the involvement of specialist heart failure physicians, nurses, interventionalists, and surgeons. In addition to medical optimisation and cardiac resynchronisation therapy, surgery plays a valuable role in many patients. We herein study the evidence and the role of surgical intervention in functional mitral regurgitation, coronary revascularisation in ischaemic cardiomyopathy, and surgical ventricular reconstruction. Additionally, we describe techniques of temporary and durable mechanical circulatory support, with their relative advantages and disadvantages, and applications. Finally, we describe the history and nomenclature around heart transplants, their indications, techniques, present-day outcomes, complications, and new developments in the field.
Keywords: mitral regurgitation